PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOLAND BAKERY PUSAT JAKARTA UTARA - Bachrudin Halim; Supardi (LPPM Universitas Asa Indonesia, 2017)
Purpose- This study aims to determine the effect of compensation, motivation and work environment on employee performance of North Jakarta Holland Bakery Central. Design/methodology/approach- In this study, the authors conducted a survey by distributing questionnaires to the employees of Holland Bakery Central North Jakarta. The number of samples in this study there are as many as 100 employees obtained by using non-random sampling technique coincidence, in which respondents who become samples are employees who are willing to fill in the questionnaire. After doing the questionnaire. For descriptive analysis method, writer use percentage analysis and mean. To test the effect of compensation, motivation and work environment, the author uses multiple linear regression analysis with F test and t test. Findings- The results of the research show the three variables together affect the performance of employees of Holland Bakery Central Jakarta North. By using t test, it was found that compensation gave significant effect to the improvement of employee's performance of North Jakarta's North Jakarta Bakery is 5.62%, while the motivation also affect the employee's performance of North Jakarta's North Jakarta Bakery is 9.24%. Work environment variables also affect the employee's performance of North Jakarta Bakery North Jakarta is 19.80%. If the three variables simultaneously found the ability of the three variables to explain the diversity of performance is 45.56%, other factors of 54.44% are not discussed in this study, including leadership style, skills, communication, training, and organizational culture, and other things .